Microbiology and Chemical Contamination Analysis of School Snacks in Bekasi - Arindah Nur Sartika; Guntari Prasetya; Maulin Inggraini; Afrinia Ekasari (Media Publikasi Cendekia Indonesia, 2026)
Elementary school children are accustomed to consuming snacks available in the school environment, sold by street vendors. The snacks consumed by school children can determine the health condition of school children due to the risk of chemical and microbiological contamination contained in these snacks. This study aimed to analyse the quality of elementary school snacks based on food safety aspects in Bekasi City. The study design was experimental study. The samples used were snacks available at four elementary schools in East Bekasi. The sample analysis included examination of Escherichia coli, Salmonella sp, borax, formalin, rhodamine B, metanil yellow, saccharin, and cyclamate with repeated examinations for each sample. The number of samples was 33 snacks. The examination results reported E. coli content in AJ iced tea (3.1 X 102; 1.4 X102) and pudding (1.4X102). All samples were declared as safe from the substances, including borax, formalin, rhodamine B, and metanil yellow. Meanwhile, saccharin content beyond the safe limit was found in es gayung mangga (mean 157.46 mg/kg), es gayung coklat (mean 118.11 mg/kg), and es teh MH (mean 131.44 mg/kg). Cyclamate content beyond the limit was found in es doger (mean 844.01 mg/kg), es lilin (mean 485.55mg/kg), es gayung coklat (mean 942.28 mg/kg), es teh MH (mean 498.05 mg/kg). From this study, it was concluded that not all elementary school snacks have been declared to meet the safe criteria according to SNI and BPOM Regulations. It is suggested to have a routine evaluation and education by the school or health officers regarding snacks available sold by street vendors in the school environment.